Understanding Elementary Students’ Mathematics Learning Difficulties: A Qualitative Analysis of Internal and External Factors - Tyas, Ni’mah Mulyaning; Rahayu, Tyas Puji; Sutrisno, Sutrisno; Muati, Sri (jurnal matematika, 2025)
Purpose of the study: This study aims to describe the factors causing mathematical difficulties. Methodology: This qualitative study involved 25 students who indicated they were having difficulty learning mathematics. Data collection techniques included observation, interviews, questionnaires, documentation, and field notes. Data analysis involved data reduction, data presentation, and drawing conclusions. Main Findings: The types of learning difficulties experienced by students include difficulty understanding the concept of fractional comparison, difficulty calculating whole numbers, and difficulty solving word problems. Factors contributing to students' learning difficulties include internal and external factors. Internal factors include negative attitudes toward learning mathematics, low motivation to learn, suboptimal physical health, and sensory impairment. External factors include a lack of variety in teaching methods, suboptimal use of learning media, school infrastructure, and family environment. Novelty/Originality of this study: Providing information about the causes of difficulties in learning mathematics that are often experienced by students, so that efforts can be made to reduce difficulties in learning mathematics.